The darkest evening [compact disc, unabridged] - Cleeves, Ann (Cleeves, Ann. Vera Stanhope series., 2020)
Discovering a toddler in an abandoned vehicle near the run-down home where her estranged father grew up, Detective Inspector Vera Stanhope approaches the property during a boisterous Christmas party before discovering the body of a woman outside.